A surfacing flux-cored welding wire and its preparation method and use
By reasonably preparing the pharmaceutical core components in the surfacing flux core welding wire, the problems of short service life and low welding efficiency of the hot forging mold after the repair of the surfacing material are solved, and an efficient and stable welding process is achieved, suitable for hot forging molds. Repair and support robotic automatic welding.
Patent Information
- Application Number
- CN202211476185.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-11-23
AI Technical Summary
The hot forging molds after repair of existing surfacing materials have short service life, low welding efficiency, a lot of welding slag, and robot welding cannot be achieved.
A kind of overlayed flux core welding wire is used, including steel strips and flux cores filled in the steel strips. The flux core consists of reducing ilmenite, rutile, ferrosilicon, potassium titanate, high carbon ferrochromium, metal chromium, manganese metal, Nickel powder and iron molybdenum are composed of which improves slag flowability, welding stability and strength, wear resistance and heat resistance of the welding layer through appropriate proportions, reducing splash and removal treatment requirements during welding.
It improves welding efficiency and wear resistance, heat fatigue resistance and temper hardness of the welding layer, realizes automatic welding of robots, and extends the service life of hot forging molds.
Smart Images

Figure CN115846932B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of welding materials, and in particular to a surfacing flux-cored welding wire and a preparation method and application thereof. Background Art
[0002] Hot forging is a forging process performed above the metal recrystallization temperature. In recent years, the automotive industry has developed rapidly, and hot forging dies are widely used in the production of automotive parts. Hot forging dies are used to hot-form parts. The working environment is harsh, and they have to withstand high temperature, high pressure and impact loads repeatedly, so their service life is short. Generally, after forging thousands of parts, various forms of failure occur, such as plastic deformation, wear, fatigue cracks, etc., which make the mold unusable or scrapped. Repairing the mold by surfacing can save a lot of expensive mold steel, simplify the processing technology, and shorten the manufacturing cycle of the mold.
[0003] However, the hot forging die repaired with existing surfacing materials has a short service life, low welding efficiency, and a lot of welding slag, and robot welding cannot be achieved. Summary of the invention
[0004] In view of the above shortcomings of the prior art, the present invention provides a surfacing flux-cored welding wire and a preparation method and use thereof, so as to improve the problems of short service life, low welding efficiency and high welding slag of the repaired hot forging die.
[0005] To achieve the above-mentioned purpose and other related purposes, the present invention provides a surfacing flux-cored welding wire, comprising a steel strip and a flux core filled in the steel strip, wherein the flux core comprises the following components, measured by mass percentage, of reduced ilmenite 3-6%, rutile 3-6%, ferrosilicon 3-6%, potassium titanate 2-4%, high carbon ferrochrome 9-13%, metallic chromium 35-41%, metallic manganese 3-5%, nickel powder 6-10%, and ferromolybdenum 19-23%.
[0006] In an example of the present invention, the titanium dioxide content in the reduced ilmenite is ≥55wt%; the titanium dioxide content in the rutile is ≥95wt%; the ferrosilicon is 75# ferrosilicon, and the silicon content in the ferrosilicon is ≥72wt%; the titanium dioxide content in the potassium titanate is ≥65wt%, and the potassium oxide content is 18-22wt%; the carbon content in the high-carbon ferrochrome is ≥8.2wt%, and the chromium content is ≥69wt%; the chromium content in the metallic chromium is ≥99wt%; the manganese content in the metallic manganese is ≥99.8wt%; the nickel content in the nickel powder is ≥99wt%; the molybdenum content in the ferromolybdenum is ≥55wt%.
[0007] In an example of the present invention, the weight of the flux core in the surfacing flux-cored welding wire is 25% to 30% of the total weight of the surfacing flux-cored welding wire.
[0008] In an example of the present invention, the steel strip has a carbon content of ≤0.04wt%, a silicon content of ≤0.03wt%, a phosphorus content of ≤0.02wt%, a sulfur content of ≤0.02wt%, a manganese content of 0.10-0.30wt%, and the balance is iron.
[0009] In an example of the present invention, the diameter of the surfacing flux-cored welding wire is 1.6 mm to 2.0 mm.
[0010] In an example of the present invention, the surfacing flux-cored wire is welded using direct current reverse connection, and the shielding gas is 80% Ar+20% CO2.
[0011] The present invention also provides a method for preparing a flux-cored welding wire, comprising the following steps: uniformly mixing the above-mentioned components to prepare a flux core; drying the flux core; rolling a steel strip into a U-shaped groove, wrapping the flux core in the U-shaped groove, and closing the groove; drawing and reducing the steel strip filled with powder to a desired specification to obtain a cladding flux-cored welding wire.
[0012] The present invention also provides a use of a surfacing flux-cored welding wire, wherein the surfacing flux-cored welding wire is used for repairing a hot forging die.
[0013] The surfacing flux-cored welding wire of the present invention adds rutile, reduced ilmenite and potassium titanate in appropriate proportions, which can improve the fluidity of slag, and there is no need to stop the arc for cleaning during welding, and at the same time, it stabilizes the arc and reduces spatter; adding high-carbon ferrochrome, metallic chromium and ferromolybdenum in appropriate proportions can improve the strength, wear resistance and hardness of the surfacing layer and the tempering stability; the appropriate proportions of ferrosilicon and nickel powder can improve the heat resistance of the surfacing layer of the surfacing flux-cored welding wire; since the phosphorus and sulfur contents in the steel strip are very low, the impurity components inside the weld can be improved, and the weld has good heat fatigue resistance, stability and wear resistance, and there is no need to stop the arc for slag cleaning during welding, the welding process is good, the welding is efficient and fast, it is suitable for hot forging die repair, and robot automatic welding can be realized. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0015] Figure 1 The present invention is a flow chart of the preparation of the cladding flux-cored welding wire. DETAILED DESCRIPTION
[0016] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.
[0017] It should be noted that "%" and "wt%" in this specification represent mass percentage, and "part" represents part by weight.
[0018] The surfacing flux-cored welding wire of the present invention comprises a steel strip and a flux core filled in the steel strip, wherein the flux core comprises the following components, measured by mass percentage of the flux core: 3-6% of reduced ilmenite, 3-6% of rutile, 3-6% of ferrosilicon, 2-4% of potassium titanate, 9-13% of high-carbon ferrochrome, 35-41% of metallic chromium, 3-5% of metallic manganese, 6-10% of nickel powder, and 19-23% of ferromolybdenum.
[0019] The functions of each component in the drug core are as follows:
[0020] Reduced ilmenite: The main component is titanium dioxide, which mainly plays a slag-making role. A proper amount of addition can also play an arc stabilizing role. It can replace a part of rutile to reduce the manufacturing cost. The mass percentage of the reduced ilmenite in the present invention is 3-6%, for example, the content of the reduced ilmenite can be any value within the range of 3-6%, such as 3%, 5% or 6%.
[0021] Rutile: The main component is titanium dioxide, which is the main slag-forming agent together with reduced titanium iron. It can improve the fluidity and coverage of the slag, stabilize the welding arc, and reduce spatter. The proper amount of rutile can ensure the full-position welding process of the flux-cored wire. Too low or too high a content is not conducive to the welding processability of the wire. The mass percentage of rutile in the present invention is 3-6%, for example, the content of rutile can be any value within the range of 3-6%, such as 3%, 4% or 6%.
[0022] Ferrosilicon and metallic manganese: silicon and manganese elements can achieve silicon-manganese joint deoxidation and desulfurization together, improve the transition coefficient of the elements, reduce the tendency to produce hot cracks, and help improve the low-temperature toughness of steel; silicon, as an alloying element, has a solid solution strengthening effect on the cladding layer metal, which can significantly improve the wear resistance of steel; silicon combined with elements such as chromium and molybdenum can also improve corrosion resistance and oxidation resistance, and can be used as an alloying element to improve heat resistance. In the present invention, the mass percentage of ferrosilicon is 3-6%, for example, the content of ferrosilicon can be any value within the range of 3-6%, such as 3%, 4% or 6%; the mass percentage of metallic manganese is 3-5%, for example, the content of metallic manganese can be any value within the range of 3-5%, such as 3%, 4% or 5%.
[0023] Potassium titanate: Increase arc voltage, increase arc blowing force, improve molten pool fluidity, and improve weld formation quality. The mass percentage of potassium titanate in the present invention is 2-4%, for example, the content of potassium titanate can be any value within the range of 2-4%, such as 2%, 3% or 4%.
[0024] High carbon ferrochrome, metallic chromium: High carbon ferrochrome transfers carbon elements to the weld metal, promoting the formation of martensite. High carbon ferrochrome and metallic chromium provide chromium elements at the same time, which increases the pitting potential of steel, promotes the formation of a passivation film on the steel surface, reduces the sensitivity of steel to pitting corrosion, and improves the wear resistance of steel; at the same time, it increases the hardenability of steel and forms M3C, M7C3, M 23 C6 and other carbides have precipitation strengthening effect, which is beneficial to improve the strength, hardness and wear resistance of steel. The mass percentage of high carbon ferrochrome in the present invention is 9-13%, for example, the content of high carbon ferrochrome can be any value in the range of 9-13%, such as 9%, 11% or 13%; the content of metal chromium is 35-41%, for example, the content of metal chromium can be any value in the range of 35-41%, such as 35%, 38% or 41%.
[0025] Nickel powder: Nickel can be infinitely dissolved in austenite, has a solid solution strengthening effect, can effectively refine the grains, and improve the corrosion resistance in acid and alkali environments; it has rust prevention and heat resistance at high temperatures. The mass percentage of nickel powder in the present invention is 6-10%, for example, the content of nickel powder can be any value within the range of 6-10%, such as 6%, 8% or 10%.
[0026] Ferro-molybdenum: Molybdenum combined with carbon and iron elements can form fine precipitates (Mo2C, Fe2Mo), which improves the strength of steel, while improving the tempering stability of steel and improving welding processability. The mass percentage of ferro-molybdenum in the present invention is 19-23%, for example, the content of ferro-molybdenum can be any value within the range of 19-23%, such as 19%, 21% or 23%.
[0027] In one embodiment, the titanium dioxide content in the reduced ilmenite is ≥55wt%; the titanium dioxide content in rutile is ≥95wt%; the ferrosilicon is 75# ferrosilicon, and the silicon content in ferrosilicon is ≥72wt%; the titanium dioxide content in potassium titanate is ≥65wt%, and the potassium oxide content is 18-22wt%; the carbon content in high carbon ferrochrome is ≥8.2wt%, and the chromium content is ≥69wt%; the chromium content in metallic chromium is ≥99wt%; the manganese content in metallic manganese is ≥99.8wt%; the amount of nickel in nickel powder is ≥99wt%, and the molybdenum content in ferromolybdenum is ≥55wt%; the particle size of each component in the core is preferably: 60 mesh of reduced ilmenite, 80 mesh of rutile, 60 mesh of ferrosilicon, 80 mesh of potassium titanate, 40 mesh of high carbon ferrochrome, 80 mesh of metallic chromium, 60 mesh of metallic manganese, 60 mesh of nickel powder, and 60 mesh of ferromolybdenum.
[0028] In one embodiment, the carbon content in the steel strip is ≤0.04wt%, the silicon content is ≤0.03wt%, the phosphorus content is ≤0.02wt%, the sulfur content is ≤0.02wt%, the manganese content is 0.10-0.30wt%, and the balance is iron.
[0029] In one embodiment, the filling rate of the flux core in the cladding flux-cored welding wire, that is, the weight of the flux core is 25% to 30% of the total weight of the cladding flux-cored welding wire. For example, the filling rate of the cladding flux-cored welding wire can be any value within the range of 25% to 30%, such as 25%, 28% or 30%.
[0030] In one embodiment, the diameter of the cladding flux-cored welding wire is 1.6 mm to 2.0 mm. For example, the diameter of the cladding flux-cored welding wire can be any value within the range of 1.6 mm to 2.0 mm, such as 1.6 mm, 1.8 mm or 2 mm.
[0031] In one embodiment, direct current reverse connection is adopted during welding with flux-cored wire, and the shielding gas is 80% Ar+20% CO2.
[0032] See also Figure 1 The present invention provides a method for preparing a cladding flux-cored welding wire, comprising the following steps:
[0033] S1. Mix the components of the drug core evenly according to the above proportions;
[0034] S2, drying the core;
[0035] S3, rolling the steel strip into a U-shaped groove, wrapping the core in the U-shaped groove, and closing it;
[0036] S4. The steel strip filled with powder is drawn and reduced in diameter to the required specification to obtain a surfacing flux-cored welding wire.
[0037] In step S1, the components in the core are mixed and stirred uniformly according to the following proportions: 3-6% reduced ilmenite, 3-6% rutile, 3-6% ferrosilicon, 2-4% potassium titanate, 9-13% high carbon ferrochrome, 35-41% metallic chromium, 3-5% metallic manganese, 6-10% nickel powder, and 19-23% ferromolybdenum.
[0038] In step S2, when drying the core, the drying temperature is 150-200°C, and the drying time is 2-3h. For example, the drying temperature can be any value within the temperature range of 150-200°C, such as 150°C, 180°C or 200°C, and the drying time can be any value within the range of 2-3h, such as 2h, 2.5h or 3h.
[0039] In step S3, the carbon content in the steel strip is ≤0.04wt%, the silicon content is ≤0.03wt%, the phosphorus content is ≤0.02wt%, the sulfur content is ≤0.02wt%, the manganese content is 0.1-0.3wt%, and the balance is iron; the size of the steel strip is preferably 0.4mm×10mm in thickness×width; the filling rate of the flux core is 25%-30%, for example, the filling rate of the surfacing flux cored welding wire can be any value within the range of 25%-30%, such as 25%, 28% or 30%.
[0040] In step S4, the diameter of the flux-cored welding wire is 1.6 mm to 2.0 mm. For example, the diameter of the flux-cored welding wire can be any value within the range of 1.6 mm to 2.0 mm, such as 1.6 mm, 1.8 mm or 2 mm.
[0041] In one embodiment, the surfacing flux-cored welding wire is used for hot forging die repair.
[0042] The present invention is described in detail below through some specific examples. The drugs used in the following examples can all be obtained through common commercial means.
[0043] Example 1
[0044] The surfacing flux-cored welding wire of this embodiment includes a steel strip and a flux core filled in the steel strip, wherein the flux core includes the following components in terms of mass percentage: 3% reduced ilmenite, 6% rutile, 6% ferrosilicon, 4% potassium titanate, 13% high carbon ferrochrome, 35% metallic chromium, 3% metallic manganese, 7% nickel powder, and 23% ferromolybdenum. The flux core is dried at 150°C for 3h, the steel strip is rolled into a U-shaped groove, and then the mixed flux core is filled into the U-shaped groove, and the filling rate of the flux core is 25%; then the welding wire is obtained by closing, reducing the diameter, drawing, and winding. The diameter of the welding wire is 1.6mm.
[0045] Example 2
[0046] The surfacing flux-cored welding wire of this embodiment includes a steel strip and a flux core filled in the steel strip, wherein the flux core includes the following components in terms of mass percentage: 5% reduced ilmenite, 5% rutile, 5% ferrosilicon, 3% potassium titanate, 13% high carbon ferrochrome, 38% metallic chromium, 4% metallic manganese, 8% nickel powder, and 19% ferromolybdenum. The flux core is dried at 180°C for 2.5h, the steel strip is rolled into a U-shaped groove, and then the mixed flux core is filled into the U-shaped groove, and the filling rate of the flux core is 26%; then the welding wire is obtained by closing, reducing the diameter, drawing, and winding. The diameter of the welding wire is 1.6mm.
[0047] Example 3
[0048] The surfacing flux-cored welding wire of this embodiment includes a steel strip and a flux core filled in the steel strip, wherein the flux core includes the following components in terms of mass percentage: 6% reduced ilmenite, 3% rutile, 3% ferrosilicon, 2% potassium titanate, 9% high carbon ferrochrome, 41% metallic chromium, 5% metallic manganese, 10% nickel powder, and 21% ferromolybdenum. The flux core is dried at 200°C for 2h, the steel strip is rolled into a U-shaped groove, and then the mixed flux core is filled into the U-shaped groove, and the filling rate of the flux core is 28%; then the welding wire is obtained by closing, reducing the diameter, drawing, and winding. The diameter of the welding wire is 1.8mm.
[0049] Example 4
[0050] The surfacing flux-cored welding wire of this embodiment includes a steel strip and a flux core filled in the steel strip, wherein the flux core includes the following components in terms of mass percentage: 4% reduced ilmenite, 4% rutile, 4% ferrosilicon, 4% potassium titanate, 10% high carbon ferrochrome, 40% metallic chromium, 5% metallic manganese, 6% nickel powder, and 23% ferromolybdenum. The flux core is dried at 180°C for 2.5 hours, the steel strip is rolled into a U-shaped groove, and then the mixed flux core is filled into the U-shaped groove, and the filling rate of the flux core is 30%; then the welding wire is obtained by closing, reducing the diameter, drawing, and winding. The diameter of the welding wire is 2 mm.
[0051] The flux core components of the cladding flux cored welding wire of the present invention are shown in Table 1. The welding processability test and the chemical composition of the deposited metal are tested on the welding wires provided in the above-mentioned Examples 1 to 4 according to relevant standards and specifications. The welding process parameters are shown in Table 2, the welding process performance is shown in Table 3, and the chemical composition of the deposited metal is shown in Table 4.
[0052] Table 1 Composition of flux-cored welding wire for cladding
[0053]
[0054]
[0055] Table 2 Welding process parameters
[0056]
[0057] Table 3 Welding process performance
[0058] After welding, the weld overlay layer is tempered at 500℃, and the hardness of the weld overlay layer before and after tempering is tested respectively. Three different points are selected for testing. The wear resistance test is to test the wear depth of the weld overlay layer after 24 hours.
[0059]
[0060] Table 4 Chemical composition of deposited metal
[0061]
[0062] The test results of Examples 1 to 4 show that the cladding flux-cored welding wire of the present invention has good electric welding process during welding, stable arc, no need to stop the arc for treatment during welding, efficient and fast welding, and has good wear resistance, heat fatigue resistance, hardness and tempering hardness.
[0063] The present invention adds a suitable proportion of rutile, reduced ilmenite, and potassium titanate to the surfacing flux-cored wire, which can improve the fluidity of the slag, and there is no need to stop the arc for cleaning during welding, and at the same time, it stabilizes the arc and reduces the spatter; adding a suitable proportion of high-carbon ferrochrome, metallic chromium, and ferromolybdenum can improve the strength, wear resistance, hardness, and tempering stability of the surfacing layer; a suitable proportion of ferrosilicon and nickel powder can improve the heat resistance of the surfacing layer of the flux-cored wire; because the phosphorus and sulfur content in the steel strip is very low, the impurity components inside the weld can be improved, and it has good thermal fatigue resistance, stability, and wear resistance. There is no need to stop the arc for slag cleaning during welding, the welding process is good, the welding is efficient and fast, it is suitable for hot forging die repair, and robot automatic welding can be realized. Therefore, the present invention effectively overcomes some practical problems in the prior art and has a high utilization value and use significance.
[0064] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A surfacing flux-cored welding wire for hot forging die repair, characterized in that: The invention comprises a steel strip and a flux core filled in the steel strip, wherein the flux core is composed of the following components in percentage by mass: 3-6% reduced ilmenite, 3-6% rutile, 3-6% ferrosilicon, 2-4% potassium titanate, 9-13% high carbon ferrochrome, 35-41% metallic chromium, 3-5% metallic manganese, 6-10% nickel powder, and 19-23% ferromolybdenum; the carbon content in the steel strip is ≤0.04 wt%, the silicon content is ≤0.03 wt%, the phosphorus content is ≤0.02 wt%, the sulfur content is ≤0.02 wt%, the manganese content is 0.10-0.30 wt%, and the balance is iron.
2. The cladding flux-cored welding wire according to claim 1, characterized in that: The titanium dioxide content in the reduced ilmenite is ≥55wt%; the titanium dioxide content in the rutile is ≥95 wt%; the ferrosilicon is 75# ferrosilicon, and the silicon content in the ferrosilicon is ≥72 wt%; the titanium dioxide content in the potassium titanate is ≥65 wt%, and the potassium oxide content is 18~22 wt%; the carbon content in the high-carbon ferrochrome is ≥8.2 wt%, and the chromium content is ≥69 wt%; the chromium content in the metallic chromium is ≥99 wt%; the manganese content in the metallic manganese is ≥99.8 wt%; the nickel content in the nickel powder is ≥99 wt%; the molybdenum content in the ferromolybdenum is ≥55 wt%.
3. The cladding flux-cored welding wire according to claim 1, characterized in that: The weight of the flux core in the cladding flux-cored welding wire is 25% to 30% of the total weight of the cladding flux-cored welding wire.
4. The cladding flux-cored welding wire according to claim 1, characterized in that: The diameter of the surfacing flux-cored welding wire is 1.6 mm to 2.0 mm.
5. The cladding flux-cored welding wire according to claim 1, characterized in that: The cladding flux-cored wire is welded by direct current reverse connection, and the shielding gas is 80% Ar+20% CO2.
6. A method for preparing a surfacing flux-cored welding wire for hot forging die repair, characterized in that: The following steps are involved: Mixing the components in claim 1 uniformly to prepare a drug core; Drying the medicine core; Rolling the steel strip into a U-shaped groove, wrapping the core in the U-shaped groove, and closing the groove; The steel strip filled with powder is drawn and reduced to the required specifications to obtain flux-cored welding wire.
7. The preparation method according to claim 6, characterized in that: The drying temperature during the drying is 150-200° C., and the drying time is 2-3 hours.
8. Use of the cladding flux-cored welding wire according to claim 1, characterized in that: The surfacing flux-cored welding wire is used for hot forging die repair.
Citation Information
Patent Citations
Surfacing flux-cored wire used for repairing hot-forging die
CN103862194A
Metal flux-cored wire for 0Cr13 ferrite stainless steel and preparation method thereof
CN104646857A
